2015
DOI: 10.1016/j.adolescence.2015.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Peer influence processes for youth delinquency and depression

Abstract: This study explores the multiple factors that account for peer influence processes of adolescent delinquency and depression using data from Waves I and II of the National Longitudinal Study of Adolescent to Adult Health (Add Health). Random-effects longitudinal negative binomial models were used to predict depression and delinquency, controlling for social connection variables to account for selection bias. Findings suggest peer depression and delinquency are both predictive of youth delinquency, while peer in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 69 publications
(57 reference statements)
3
57
0
1
Order By: Relevance
“…Depression resulting in antisocial conducts is more pronounced for young individuals, though. There is accumulating evidence that depression can be predictors of youth delinquency [9,10]. Similarly, Anderson et al [11] reported that depressed adolescents have a substantially increased probability of involvement in property crime, while there was little evidence concerning the likelihood of engaging in violent crime or the selling of illicit drugs in their study.…”
Section: Introductionmentioning
confidence: 85%
“…Depression resulting in antisocial conducts is more pronounced for young individuals, though. There is accumulating evidence that depression can be predictors of youth delinquency [9,10]. Similarly, Anderson et al [11] reported that depressed adolescents have a substantially increased probability of involvement in property crime, while there was little evidence concerning the likelihood of engaging in violent crime or the selling of illicit drugs in their study.…”
Section: Introductionmentioning
confidence: 85%
“…Young people's emotional bonds strengthen as they spend time together, be it at school or elsewhere. In the presence of attachment to peers, young people are more willing to modify their behaviours to fit with those of the peer group (Reynolds & Crea, 2015). Through spending time together, the ASEP youth and their peers at times spontaneously decided to engage in truancy, a behaviour that weakens their school bonds but appears as a more attractive alternative to school attendance.…”
Section: Discussionmentioning
confidence: 99%
“…The task of responding prosocially when faced with bullying can be a daunting call for these youth because the intervention's focus is on changing their behaviour per se and not that of their peers. However, Reynolds and Crea (2015) found that self-regulation is an effective strategy for negotiating peer influence and building resilience. Self-regulation provides the young person with skills to navigate through challenging social contexts (Reynolds & Crea, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations